Growth Performance and Clinicopathological Analyses in Lambs Repetitively Inoculated with Aluminum-Hydroxide Containing Vaccines or Aluminum-Hydroxide Only - Ricardo de Miguel; Javier Asín; Ana Rodríguez-Largo; Irache Echeverría; Delia Lacasta; Pedro Pinczowski; Marina Gimeno; Jéssica Molín; Antonio Fernández; Ignacio de Blas; Damián de Andrés; Marta Pérez; et al. (Animals, 2021)
Aluminum (Al) hydroxide is an effective adjuvant used in sheep vaccines. However, Al-adjuvants have been implicated as potential contributors to a severe wasting syndrome in sheep—the so-called ovine autoimmune-inflammatory syndrome induced by adjuvants (ASIA syndrome). This work aimed to characterize the effects of the repetitive injection of Al-hydroxide containing products in lambs. Four flocks (Flocks 1–4; n = 21 each) kept under different conditions were studied. Three groups of seven lambs (Vaccine, Adjuvant-only, and Control) were established in each flock. Mild differences in average daily gain and fattening index were observed, indicating a reduced growth performance in Vaccine groups, likely related to short-term episodes of pyrexia and decreased daily intake. Clinical and hematological parameters remained within normal limits. Histology showed no significant differences between groups, although there was a tendency to present a higher frequency of hyperchromatic, shrunken neurons in the lumbar spinal cord in the Adjuvant-only group. Although Al-hydroxide was linked to granulomas at the injection site and behavioral changes in sheep, the results of the present experimental work indicate that injected Al-hydroxide is not enough to fully reproduce the wasting presentation of the ASIA syndrome. Other factors such as sex, breed, age, production system, diet or climate conditions could play a role.